Advertisement Remove all ads

Solve A^2x^2 - B^2 = 0 - Mathematics

Sum

Solve `a^2x^2 - b^2 = 0`

Advertisement Remove all ads

Solution

`a^2x^2 - b^2 = 0`

`=> (ax)^2 - b^2 = 0`

=> (ax + b)(ax - b) = 0

If ax + b = 0 and ax- b = 0

then `x = (-b)/a  and x= b/a`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 5 Quadratic Equations
Exercise 5 (E) | Q 3 | Page 66
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×